2015
DOI: 10.3171/2015.3.spine14716
|View full text |Cite
|
Sign up to set email alerts
|

High-dose proton-based radiation therapy in the management of spine chordomas: outcomes and clinicopathological prognostic factors

Abstract: OBJECT Spinal chordomas can have high local recurrence rates after surgery with or without conventional dose radiation therapy (RT). Treatment outcomes and prognostic factors after high-dose proton-based RT with or without surgery were assessed. METHODS The authors conducted a retrospective review of 126 treated patients (127 lesions) categorized according to disease status (primary vs recurrent), resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 24 publications
5
119
2
Order By: Relevance
“…Moreover, prior studies have often focused on single, static 5-or 10-year overall survival or disease-free survival determined at the time of diagnosis [26,34,37]. In addition, prognostic factors or risk factors have been analyzed without taking into consideration the possibility of change in prognosis with time [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, prior studies have often focused on single, static 5-or 10-year overall survival or disease-free survival determined at the time of diagnosis [26,34,37]. In addition, prognostic factors or risk factors have been analyzed without taking into consideration the possibility of change in prognosis with time [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…The overall results of the series of Rotondo et al 22 are presented above in the surgical section. With respect to RT, patients received a median dose of 72.4 GyRBE (relative biological effectiveness) as a combination of photons and protons.…”
Section: Resultsmentioning
confidence: 98%
“…Rotondo et al 22 reviewed 126 cases of chordoma of the mobile spine and sacrum of which 32 comprised LR disease. For all patients, the 5-year rate of local control (LC) was higher after radical en bloc excision (72%) than that after intralesional resection (55%) ( P =0.016).…”
Section: Resultsmentioning
confidence: 99%
“…Another systematic review also concluded that proton therapy improves long-term local control and survival in patients with skull base chordoma 65 . In tumors of the sacrum and spine, surgical resection coupled with proton therapy provided a 5-year overall survival and local control rate of 81% and 62%, respectively 66 . Carbon ion beam appears to be comparable to proton therapy.…”
Section: Treatmentmentioning
confidence: 99%